Sensitivity of the NIH Toolbox to Detect Cognitive Change in Individuals With Intellectual and Developmental Disability. (21st February 2023) - Shields, Rebecca H.; Kaat, Aaron; Sansone, Stephanie M.; Michalak, Claire; Coleman, Jeanine; Thompson, Talia; McKenzie, Forrest J.; Dakopolos, Andrew; Riley, Karen; Berry-Kravis, Elizabeth; Widaman, Keith F.; Gershon, Richard C.; et al.
Abstract : Background and Objective: Individuals with intellectual disability (ID) experience protracted cognitive development compared with typical youth. Sensitive measurement of cognitive change in this population is a critical need for clinical trials and other intervention studies, but well-validated outcome measures are scarce. This study's aim was to evaluate the sensitivity of the NIH Toolbox Cognition Battery (NIHTB-CB) to detect developmental changes in groups with ID—fragile X syndrome (FXS), Down syndrome (DS), and other ID (OID)—and to provide further support for its use as an outcome measure for treatment trials. Methods: We administered the NIHTB-CB and a reference standard cross-validation measure (Stanford-Binet Intelligence Scales, Fifth Edition [SB5]) to 256 individuals with FXS, DS, and OID (ages 6–27 years). After 2 years of development, we retested 197 individuals. Group developmental changes in each cognitive domain of the NIHTB-CB and SB5 were assessed using latent change score models, and 2-year growth was evaluated at 3 age points (10, 16, and 22 years). Results: Overall, effect sizes of growth measured by the NIHTB-CB tests were comparable with or exceeded those of the SB5. The NIHTB-CB showed significant gains in almost all domains in OID at younger ages (10 years), with continued gains at 16 years and stability in early adulthood (22 years). The FXS group showed delayed gains in attention and inhibitory control compared with OID. The DS group had delayed gains in receptive vocabulary compared with OID. Unlike the other groups, DS had significant growth in early adulthood in 2 domains (working memory and attention/inhibitory control). Notably, each group's pattern of NIHTB-CB growth across development corresponded to their respective pattern of SB5 growth. Discussion: The NIHTB-CB is sensitive to developmental changes in individuals with ID. Comparison with levels and timing of growth on the cross-validation measure shows that the NIHTB-CB has potential to identify meaningful trajectories across cognitive domains and ID etiologies. Sensitivity to change within the context of treatment studies and delineation of clinically meaningful changes in NIHTB-CB scores, linked to daily functioning, must be established in future research to evaluate the battery more completely as a key outcome measure.